Ribotype analysis of Pseudomonas pseudomallei isolates. - Sexton, M; Goebel, L; Godfrey, A; Choawagul, W; White, N; Woods, D (1993)
No epidemiological typing system to differentiate among Pseudomonas pseudomallei isolates has been available. Ribotype analysis was developed and used to examine 74 clinical and 10 environmental isolates of P. pseudomallei from Thailand. Six P. pseudomallei ribotypes were identified from restriction fragment polymorphisms of EcoRI chromosomal digests. The predominant ribotype, A, was found in 59 of the isolates examined. By using patterns from hybridizations with SalI, HindIII, and PstI restriction digests, isolates of ribotype A were subdivided into a further five subtypes, giving a total of 10 differentiable P. pseudomallei types. In 23 of 34 melioidosis patients studied, multiple P. pseudomallei isolates were present. In all but one of these patients, a single ribotype of the organism was present. Isolation of two different ribotypes of P. pseudomallei from one patient, one each in sputum and urine, suggests that superinfection may have occurred. The ribotype was shown to be conserved during the course of antibiotic treatments in seven patients studied, although the antibiotic sensitivity patterns in the isolates from these patients varied. The prevalence of subtype A1 in clinical and environmental specimens suggests that this strain may be predominant in this geographical location. These results demonstrate the usefulness of the ribotyping method for epidemiological studies of P. pseudomallei.